Economic Empowerment Through Islamic Financial Inclusion: The Strategic Role of Universities in Synergy with Islamic Financial Institutions - Rantaprasaja, Luthfi (Diversity: Jurnal Ilmiah Pascasarjana, 2025)
This paper aims to examine the strategic role of universities in promoting Islamic financial inclusion as a means of economic empowerment, particularly in the Parung Panjang area of Bogor Regency. The study employs a qualitative approach, utilizing exploratory, case study, and action research methods. Data collection involves in-depth interviews with experts, academics, and practitioners in the field of financial inclusion, as well as focus group discussions and document analysis. The research explores how universities can leverage the Tridharma of Higher Education to bridge the gap between Islamic financial institutions and local micro and small businesses (MSMEs). Findings indicate that while financial literacy, accessibility barriers, and institutional coordination remain key challenges, universities can play a pivotal role in promoting Islamic financial inclusion. This can be achieved through developing financial literacy programs, conducting applied research, establishing industry partnerships, and providing direct financial assistance to MSMEs. The research highlights the significant impact of Islamic financial inclusion in enhancing community welfare. It emphasizes the importance of collaboration between higher education institutions and Islamic financial organizations to foster economic development and reduce financial disparities. This study contributes to the literature by comprehensively examining the strategic role of universities in forming, supporting, and developing Islamic financial inclusion initiatives, an area that has been less explored in previous research. It provides valuable insights into how universities can become a driving force to encourage economic empowerment through Islamic financial inclusion, potentially creating a broad positive impact on society, particularly in regions with significant economic disparities.